Anchoring Co3S4 nanowires on NiCo2O4 nanosheet arrays as high-performance electrocatalyst for hydrogen and oxygen evolution. Issue 37 (7th September 2022) - Wei, Hao; Jiu, Hongfang; Che, Sicong; Wang, Congli; Guo, Zhixin; Han, Yuxin; Qin, Yaqi; Zhang, Lixin
Abstract : The NF/NiCo2 O4 /Co3 S4 exhibits surprising electrocatalytic activity. Abstract : The development of catalysts which can substitute expensive metals to efficiently split water is currently a hot research topic. Here, a multi-layered NF/NiCo2 O4 /Co3 S4 nanocomposite was prepared on 3D porous nickel foam by hydrothermal and annealing processes. The electrode is a multi-layered, highly conductive and high specific surface area network without a binder, which facilitates electron transport and exposure of active sites, enhances full contact of the electrolyte/electrode interface, and accelerates H2 and O2 diffusion during water electrolysis. As expected, NF/NiCo2 O4 /Co3 S4 exhibits surprising electrocatalytic activity, and only required 71 and 170 mV to reach 10 mA cm −2 in the hydrogen and oxygen evolution reactions, respectively, and exhibited stability up to 36 h. This strategy provides an efficient, durable, and low-cost bifunctional catalyst.